The role of the first-year experience in student attrition. Issue 3 (1st September 2020) - Shcheglova, Irina; Gorbunova, Elena; Chirikov, Igor
ABSTRACT: Quality assurance in higher education often emphasises the importance of lowering student attrition. The first year of study is a crucial period for mitigating risks of attrition as this is the time when students develop a sense of belonging, and academic and personal connections. This study explores the long-term effects of the first-year student experience on attrition during their four years of study using two longitudinal datasets from a highly selective Russian university. First-year student data from the Student Experience in the Research University (SERU) survey for two cohorts of students with graduation data four years later were combined to identify factors that increase attrition. Student disengagement and lower academic aspirations during the first year of study are associated with student attrition in both cohorts. Policy implications of the findings for Russia and post-communist higher education systems with attrition linked to academic performance are discussed.